(untitled) (Konferensiyalar | Conferences, 2024)
This qualitative study explores the impact of ethnic and cultural factors on modern teaching education. Through in-depth interviews with experienced educators, themes emerged highlighting the importance of cultural awareness, challenges in addressing diversity, strategies for inclusivity, and the positive impact of culturally relevant teaching practices on student engagement and learning outcomes. Recommendations are provided to enhance cultural competence among educators, promote curriculum inclusivity, and foster partnerships with communities. Embracing ethnic and cultural diversity in education is essential for creating equitable and enriching learning environments.